Sensitivity and Specificity of Ultrasonography in Diagnosis of Acute Appendicitis - A Mohammadi (Babol University of Medical Sciences, 2009)
BACKGROUND AND OBJECTIVE: Acute appendicitis is one of the most important urgent conditions of abdominal surgery, in which, proper and on-time diagnosis may decrease the unwanted complications. In despite of diagnostic methods, a significant number of patients yet end up with negative laparotomies. Sonography can diminish the rate of these negative results. The aim of this study was to evaluate the sensitivity and specificity of sonography in diagnosis of acute appendicitis. METHODS: In a cross sectional study, 500 patients with acute abdomen and primary diagnosis of acute appendicitis were evaluated preoperatively by graded compression sonography. This study was conducted in Tabriz Imam Khomeini hospital during 12 months. Results of sonography were compared with histopathological findings after operation. FINDINGS: A hundred and sixty three males and 237 females with the mean age of 25.1±13.9 years were enrolled. Sensitivity, specificity, PPV, NPV and accuracy of abdominal sonography in diagnosis of acute appendicitis were 96.2, 93.1, 96.8, 91.9 and 95.2 percent, respectively 97.2, 96.4, 98.3, 94.2 and 97 percent, respectively in males and 95, 89.5, 95, 89.5 and 93.2 percent, respectively in females. The optimal cut-off point of diameter of appendix was ≥5.8 mm with corresponding sensitivity and specificity of 88.3% and 73%, respectively.CONCLUSION: Due to noninvasiveness, cost-effectiveness and availableness of sonography, it is proposed as a diagnostic modality. This may cause a dramatic decrease in the costs of operation and treatment of patients.